Identifying the Conditions for Cost-Effective Minimally Invasive Neurosurgery in Spontaneous Supratentorial Intracerebral Hemorrhage - Schreuder, Floris H. B. M.; Scholte, Mirre; Ulehake, Marike J.; Sondag, Lotte; Rovers, Maroeska M.; Dammers, Ruben; Klijn, Catharina J. M.; Grutters, Janneke P. C. (Frontiers in Neurology, 2022)
Background: In patients with spontaneous supratentorial intracerebral hemorrhage (ICH), open craniotomy has failed to improve functional outcome. Innovative minimally-invasive neurosurgery (MIS) may improve health outcome and reduce healthcare costs. Aims: Before starting phase-III trials, we aim to assess conditions that need to be met to reach potential cost-effectiveness of MIS compared to usual care in patients with spontaneous supratentorial ICH. Methods: We used a state-transition model to determine at what effectiveness and cost MIS would become cost-effective compared to usual care in terms of quality-adjusted life-years (QALYs) and direct healthcare costs. Threshold and two-way sensitivity analyses were used to determine the minimal effectiveness and maximal costs of MIS, and the most cost-effective strategy for each combination of cost and effectiveness. Scenario and probabilistic sensitivity analyses addressed model uncertainty. Results: Given €10,000 of surgical costs, MIS would become cost-effective when at least 0.7-1.3% of patients improve to a modified Rankin Scale (mRS) score of 0-3 compared to usual care. When 11% of patients improve to mRS 0-3, surgical costs may be up to €83,301-€164,382, depending on the population studied. Cost-effectiveness of MIS was mainly determined by its effectiveness. In lower mRS states, MIS needs to be more effective to be cost-effective compared to higher mRS states. Conclusions: MIS has the potential to be cost-effective in patients with spontaneous supratentorial ICH, even with relatively low effectiveness. These results support phase-III trials to investigate the effectiveness of MIS.